Implementation of Discovery Learning Model to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 7 Kuala Batee - Nuraidar; Asyimah, Nur (Journal of Indonesian Primary School, 2025)
This study aims to examine the impact of the Discovery Learning model in improving students' academic achievement and motivation in Islamic Education learning at SDN 7 Kuala Batee. The research design used was a quasi-experimental study, with two groups of 5th grade students, namely the experimental group who received learning using the Discovery Learning model and the control group who continued with traditional lecture-based learning. This study used pre- and post-assessments, classroom observations, and student surveys to measure academic achievement, engagement, and motivation. The results showed that students in the experimental group experienced significant improvements in their ability to remember and apply Islamic teachings, especially in real-life situations. In addition, students in the experimental group were more engaged and reported higher levels of motivation compared to the control group. These findings suggest that Discovery Learning encourages active participation, critical thinking, and collaborative problem solving, which results in a deeper understanding of the material. Although there were some challenges, such as time management and ensuring equal participation from all students, the overall results indicate that the Discovery Learning model is effective in improving student learning outcomes and motivation. Based on these findings, it is recommended that the Discovery Learning model be implemented and expanded in the curriculum to create a more interactive and student-centered learning environment. This study highlights the importance of active learning methods in improving student engagement and academic achievement. The results of the study also show that Discovery Learning can be useful in other subjects and different educational contexts, paving the way for further research into its wider application and long-term impact.